Medicaid enrollment after liver transplantation: Effects of medicaid expansion. Issue 8 (August 2016) - Tumin, Dmitry; Hayes, Don; Washburn, W. Kenneth; Tobias, Joseph D.; Black, Sylvester M.
Abstract : Liver transplantation (LT) recipients in the United States have low rates of paid employment, making some eligible for Medicaid public health insurance after transplant. We test whether recent expansions of Medicaid eligibility increased Medicaid enrollment and insurance coverage in this population. Patients of ages 18‐59 years receiving first‐time LTs in 2009‐2013 were identified in the United Network for Organ Sharing registry and stratified according to insurance at transplantation (private versus Medicaid/Medicare). Posttransplant insurance status was assessed through June 2015. Difference‐in‐difference multivariate competing‐risks models stratified on state of residence estimated effects of Medicaid expansion on Medicaid enrollment or use of uninsured care after LT. Of 12, 837 patients meeting inclusion criteria, 6554 (51%) lived in a state that expanded Medicaid eligibility. Medicaid participation after LT was more common in Medicaid‐expansion states (25%) compared to nonexpansion states (19%; P < 0.001). Multivariate analysis of 7279 patients with private insurance at transplantation demonstrated that after the effective date of Medicaid expansion (January 1, 2014), the hazard of posttransplant Medicaid enrollment increased in states participating in Medicaid expansion (hazard ratio [HR] = 1.5; 95% confidence interval [CI] = 1.1‐2.0; P = 0.01), but not in states opting out of Medicaid expansion (HR = 0.8; 95% CI = 0.5‐1.3; P = 0.37), controlling for individual characteristics and time‐invariant state‐level factors. No effects of Medicaid expansion on the use of posttransplant uninsured care were found, regardless of private or government insurance status at transplantation. Medicaid expansion increased posttransplant Medicaid enrollment among patients who had private insurance at transplantation, but it did not improve overall access to health insurance among LT recipients. Liver Transplantation 22 1075–1084 2016 AASLD